Building Information Modelling in mechanised shield tunnelling: a practitioner's outlook to the near future - Stascheit, Janosch; Ninić, Jelena; Meschke, Günther; Hegemann, Felix; Maidl, Ulrich (Ernst und Sohn, 2018)
The contribution takes a glance at the application of BIM technologies in the design and construction phases of shield tunnelling projects. The intention is to show how Building Information Modelling can be translated into actual benefit, not only in the operation phase but also in the design and construction phases of bored tunnels. Emphasising the integrative character of referencing data uniformly in space and time, examples are given of seamless communication between 3D geometrical modelling, efficient numerical simulation and model adaptation based on measured data acquired during the boring process. The article covers the complete range from predesign through structural analysis and detailed design until the actual excavation process including its interactions with the environment. Special emphasis is given to data management, which is the key to transforming a mere 3D visualisation into a Building Information Model. The article therefore presents a concept for database-supported, webbased integration of software modules for geometrical modelling in various levels of detail, efficient numerical simulation tools that are based upon this representation, and process controlling that manages all data acquired during the construction process in a spatially and temporally coordinated reference system.